2017
DOI: 10.1002/vnl.21608
|View full text |Cite
|
Sign up to set email alerts
|

Polyether polyol‐based rigid polyurethane foams reinforced with soy protein fillers

Abstract: In this work, soy protein/polyurethane (PU) composite foams were synthesized with polyether polyol and polyaryl polymethylene isocyanate as the starting materials, soy protein isolate as the reactive fillers, and water as the blowing agent. The structure and properties of the resulting composite foams were characterized by Fourier transform infrared spectra, scanning electron microscope, close cell ratio, density, mechanical properties, and so on. Strong hydrogen bonding interactions as well as chemical crossl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…When compared with neat PUR_0, the addition of HS fillers results in the production of PUR foams with higher values of T 2% , which refers to the release of volatile products presented in the HS fillers. Previous studies have reported that cellulosic fillers tend to degrade in the range of lower temperatures, thus a higher value of T 2% should be attributed to the partial crosslinking between functional groups of HS fillers and isocyanate groups [ 61 ]. The second degradation of mass loss occurs in the range of 309–326 °C and refers to the thermal decomposition of hard segments—urethane bonds [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…When compared with neat PUR_0, the addition of HS fillers results in the production of PUR foams with higher values of T 2% , which refers to the release of volatile products presented in the HS fillers. Previous studies have reported that cellulosic fillers tend to degrade in the range of lower temperatures, thus a higher value of T 2% should be attributed to the partial crosslinking between functional groups of HS fillers and isocyanate groups [ 61 ]. The second degradation of mass loss occurs in the range of 309–326 °C and refers to the thermal decomposition of hard segments—urethane bonds [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the release of volatile products from the polyurethane matrix increases with the addition of the fibers [93]. Taking this into account, the volatile products of biodegradable fibers tend to release at lower temperatures, the higher values of T2% may be connected with partial crosslinking between filler's functional groups and isocyanate groups (-NCO) [94]. This effect is more prominent for foams modified with chemically-treated fibers.…”
Section: Thermogravimetric Analysis Of Polyurethane Foamsmentioning
confidence: 98%
“…Additionally, chemically-treated fibers can act as a cross-linker between PUR backbones, consequently enhancing the thermal properties of the foam. Tian et al [94] reported that the enhancement of thermal stability of the soy-protein enhanced foams is may be attributed to the crosslinking effect of soy protein on the matrix, which prevents the volatile products generated during thermal decomposition, leading to the retardance of the thermal degradation action. A similar effect can be found in the presented work.…”
Section: Flammability Of Polyurethane Foamsmentioning
confidence: 99%
“…Soy protein isolate (SPI) is one kind of plant protein with high quality and low cost . In addition to food application areas, soy protein based biomaterials are attracting more and more attention for their eco‐friendly characters . Pure soy protein possesses poor thermoplasticity due to the abundant hydrogen bonding interactions .…”
Section: Introductionmentioning
confidence: 99%